A framework for rapid virtual prototyping: a case study with the Gunnerus research vessel. Issue 1 (2nd January 2023) - Major, Pierre; Zghyer, Rami; Zhang, Houxiang; Hildre, Hans Petter
ABSTRACT: Virtual prototypes (VPs) are digital models that mock-up existing or conceptual systems' behaviour. In offshore operations, VPs find usages in design, proof of concept for new equipment or method, control system testing, procedure planning, and expert crew training. Moreover, VP can be used in full mission simulators with crews of maritime and offshore engineers, in which case they integrate with control systems such as handles and dynamic positioning systems. Putting the human in the loop sets high requirements for the fidelity of the visual 3D-models and the mathematical models' validity. VPs are thus time-consuming to create and difficult to validate, even based on an existing offshore system. This paper presents an innovative framework for rapid virtual prototyping of ships for hardware and human in the loop simulations and validates the results with data gathered in a sea trial performed on a research vessel, with satisfying results for position keeping. Abbreviations: CLI, Command line interpreter; DP, Dynamic positioning system: ship equipment used to maintain position and heading; DM, Damping matrix; Force FBK, Force Feedback Thruster1; HIL, Hardware in the loop; HITL, Human in the loop; JNI, Java native interface; LC, Loading condition; RAO, Response amplitude operator; RPM, Revolutions per minute; RPM FBK, RPM Feedback Thruster2/3 (Main/Azimuth); SCM, Source code management system; SOG, Speed over ground; VP, Virtual prototyping/prototype; VST, Virtual sea trial; sea trial performed in a simulation